Giant lipoma on lower lip: an unusual case - Victor Yuri Nicolau Ferreira; Laudenice de Lucena Pereira; Dasaiev Monteiro Dutra; Emanuene Galdino Pires; Larissa Cavalcanti Monteiro; Danyel Elias da Cruz Perez; Paulo Rogério Ferreti Bonan (Editorial Ciencias Médicas, 2017)
Introduction: lipomas are benign mesenchymal tumors which consist essentially of mature adipocytes, and are relatively uncommon in the oral cavity comparing with other body surfaces. Large lesions are relatively rare and lower lip is not a very usual site. This is characterized as a slow growing lesion which might reach large dimensions and are usually asymptomatic. Objective: to show a case of giant lipoma affecting lower lip and to comment on its clinical and microscopic features. Case report: in this study, we describe a case of giant lipoma affecting lower lip of a 55 years-old male with an asymptomatic evolution of eight years. We performed a complete excision, and the histopathological examination revealed a lipoma. Conclusions: actually, the patient is under follow up without signs of recurrence. The clinical and microscopic characteristics were very important for the diagnosis.